MAKNA AHL AL-KITAB DALAM AL-QUR’AN (SUATU KAJIAN TAFSIR TEMATIK) - Syamruddin Nasution (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
One of the controversial in interfaith marriage is a sense Ahl al-Kitab. There are differences of understanding between the scholars who actually Ahl al-Kitab is because the meaning of Ahl al-Kitab has sects or groups in their causes differ in interpreting the verses of the Koran. This stutdy will examine it through thematic interpretation methods, through Tafsir Al-Azhar and Tafsir Al-Mishbah